δ13C OF LOW-MOLECULAR-WEIGHT ORGANIC ACIDS GENERATED BY THE HYDROUS PYROLYSIS OF OIL-PRONE SOURCE ROCKS - Dias R.F.; Freeman K.H.; Lewan M.D.; Franks S.G. (My University, 2002)
Low-molecular-weight (LMW) aqueous organic acids were generated from six oil-prone source rocks under hydrous-pyrolysis conditions. Differences in total organic carbon-normalized acid generation are a function of the initial thermal maturity of the source rock and the oxygen content of the kerogen (OI). Carbon-isotope analyses were used to identify potential generation mechanisms and other chemical reactions that might influence the occurrence of LMW organic acids. The generated LMW acids display increasing 13C content as a function of decreasing molecular weight and increasing thermal maturity. The magnitudes of observed isotope fractionations are source-rock dependent. These data are consistent with δ13C values of organic acids presented in a field study of the San Joaquin Basin and likely reflect the contributions from alkyl-carbons and carboxyl-carbons with distinct δ13C values. The data do not support any particular organic acid generation mechanism. The isotopic trends observed as a function of molecular weight, thermal maturity, and rock type are not supported by either generation mechanisms or destructive decarboxylation. It is therefore proposed that organic acids experience isotopic fractionation during generation consistent with a primary kinetic isotope effect and subsequently undergo an exchange reaction between the carboxyl carbon and dissolved inorganic carbon that significantly influences the carbon isotope composition observed for the entire molecule. Although generation and decarboxylation may influence the δ13C values of organic acids, in the hydrous pyrolysis system described, the nondestructive, pH-dependent exchange of carboxyl carbon with inorganic carbon appears to be the most important reaction mechanism controlling the δ13C values of the organic acids.